Physical activity in professional training of physiotherapists - Frömel, Karel; Dygrýn, Jan; Vorlíček, Michal; Jakubec, Lukáš; Groffik, Dorota; Smékal, David; Mitáš, Josef (Annals of medicine, 2025)
BACKGROUND: The current negative trend in the physical behavior and lifestyle of the population therefore requires adequate changes in the professional training of physiotherapists. OBJECTIVES: This study aimed to determine the structure and differences in the weekly physical activity (PA) of Czech physiotherapy students, the use of wearables in physiotherapy professional training, and the attitude of physiotherapy students toward PA and the use of wearables in physiotherapy practice. METHODS: Between 2013 and 2022, 412 physiotherapy students participated in a PA-monitoring study using questonnaires International Physical Activity Questionnaire-long form, Motives for Physical Activity Measure-Revise, pedometers, Garmin Vívofit and Axivity AX3 accelerometers. RESULTS: A retrospective analysis of physiotherapy students PA drew attention to insufficient weekly PA and insufficient achievement of the PA recommendation of at least 60 min five times a week (55% of men and 41% of women). Instrumental PA monitoring allowed analyzing individual daily PA and structure of weekly PA. Highest PA indicated men (14,102 steps/day) and women (12,724 steps/day) of the 1st study year on Tuesday. The lowest PA (9,488 steps/day for men and 8,815 steps/day for women), were observed in the 4th study year on Sundays. The recommended target of 11,000 steps per day was achieved by 40% of the men and 46% of the women. Wearables enhanced participants PA motivation (51%). CONCLUSIONS: The inclusion of weekly PA monitoring in the professional training of physiotherapists ensured a deeper insight into the possibilities of PA monitoring in physiotherapy practice . Students are prepared to use wearables more widely to improve physical therapy practice.
Keywords: průzkumy a dotazníky; Adult; cvičení; professional education; Attitude of Health Personnel; Česká republika; lifestyle; Humans; ženské pohlaví; mladý dospělý; dospělí; Female; retrospektivní studie; Physical Therapists; Male; mužské pohlaví; Young Adult; Exercise; fyzioterapeuti; monitoring; Motivation; wearables; Retrospective Studies; Czech Republic; Physical activity; lidé; postoj zdravotnického personálu; motivace; Surveys and Questionnaires